Evaluating Adverse Events and Management Strategies in Foam Sclerotherapy: A Case Report of Sinus Venosus Atrial Septal Defect - Kudret Atakan Tekin; Ufuk Türkmen (Hitit Medical Journal)
ABSTRACTFoam sclerotherapy (FS) is widely employed for minimally invasive varicose vein treatment. Despite contraindications in symptomatic right-to-left shunt cases like patent foramen ovale, routine pre-procedure transthoracic echocardiogram (TTE) screening isn't standard. This article discusses managing chest symptoms during FS in a young woman later diagnosed with an unknown sinus venosus atrial septal defect (SV-ASD). FS was administered to a 38-year-old female with symptomatic CEAP-1, who developed chest symptoms. Subsequent diagnosis revealed SV-ASD. Minimally invasive repair followed four weeks later. While FS is generally safe, it poses systemic adverse event risks, emphasizing vigilance in managing SV-ASD patients undergoing FS.